1979
DOI: 10.2337/diab.28.10.949
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Susceptibility to Diabetes Mellitus: the Distribution of Properdin Factor B (Bf) and Glyoxalase (GLO) Phenotypes

Abstract: SUMMARYThe distribution of phenotypes controlled by two loci on chromosome 6 has been studied in a series of 239 patients with type 1 (insulin-dependent) and 297 patients with type 2 (non-insulin-dependent) diabetes mellitus. At the properdin factor B (Bf) locus there is a significant increase in the frequency of the Bf s1 and Bf n alleles for type 1 patients, and the combined increase in frequency of Bf s^ and Bf F1 in those patients is highly significant. The relative risk for F1 is 6.2 and for F1 and S1 com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1982
1982
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 5 publications
1
10
0
Order By: Relevance
“…Type 1 (insulin-dependent) diabetes mellitus has been shown to be associated with HLA, factor B (BI) and complement component C4 in various white populations [7,9,11,13,20,23]. With the exception of C4 similar findings have been reported for black Americans with Type i diabetes [5,17,19,25].…”
supporting
confidence: 68%
“…Type 1 (insulin-dependent) diabetes mellitus has been shown to be associated with HLA, factor B (BI) and complement component C4 in various white populations [7,9,11,13,20,23]. With the exception of C4 similar findings have been reported for black Americans with Type i diabetes [5,17,19,25].…”
supporting
confidence: 68%
“…Other studies have not found changes in GLO 1-1 phenotype or GLO' allele frequency in insulindependent diabetic patients (Tokanaga et al, 1982;Kirk et al, 1985). For non-insulin-dependent diabetic patients, Kirk et al (1979) found an excess of GLO 2-2 phenotype and a deficiency of GLO 1-2 phenotype whereas other surveys (Kirk et al, 1985;McCann et al, 1981) produced no significant difference. However, more interestingly, insulin-dependent diabetic patients without clinical complications had a significant excess of the homozygote GLO 1-1 whereas patients with complications did not (McCann et al, 1981).…”
Section: Biological Effects Of Methylglyoxalmentioning
confidence: 88%
“…This deviation from Hardy-Weinberg equilibrium, which has been also reported in other populations (43), suggests the existence of yet unknown selection forces. Of note, this SNP has also been associated with diseases leading to decreased life expectancy such as prostate cancer and diabetes (44)(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%